Resistance to Azoles in Candida parapsilosis Isolates from Spain Is Associated with an Impairment in Filamentation and Biofilm Formation - Alba Torres-Cano; Cristina de Armentia; Alejandra Roldán; Elena López-Peralta; Juliana Manosalva; Paloma Merino-Amador; Fernando González-Romo; Mireia Puig-Asensio; Carmen Ardanuy; María Teresa Martín-Gómez; Daniel Romero-Herrero; Ana Pérez-Ayala; et al. (Journal of Fungi)
In recent years, there has been an increase in the incidence of fluconazole-non-susceptible (FNS) Candida parapsilosis. The reasons why these strains are able to colonize hospitals remain unknown. It is also unclear whether these strains exhibit resistance to the disinfectants used in hospitals, facilitating their spread. For these reasons, in this work, we aimed to investigate whether fluconazole resistance was associated with virulence traits and the resistance of these strains to common hospital disinfectants. The general conclusion of the study was that more than 95% of the FNS strains, regardless of the resistance mutation they carried, had filamentation problems, whereas around 75% of the susceptible strains formed pseudohyphae and were capable of filamentation. This 95% of the FNS strains did not form pseudohyphae, did not invade agar, and did not form biofilms, while the susceptible strains exhibited the opposite behaviour. Through microfluidics experiments, we observed that both the susceptible and FNS strains were capable of adhering to a plastic surface under dynamic conditions, but the FNS strains formed unstable aggregates that did not remain attached to the surface, confirming the filamentation defect of these strains. In the second part of the study, we observed that FNS strains are susceptible to clinical disinfectants, although they presented a slight resistance to some of them, such as chlorhexidine, compared to susceptible isolates. In this work, we address important aspects to understand the dissemination of FNS strains in clinical outbreaks.